1997
DOI: 10.1002/(sici)1096-9896(199703)181:3<281::aid-path777>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Genetic heterogeneity in sporadic colorectal adenomas

Abstract: The majority of colorectal cancers develop from adenomatous polyps under the influence of factors that are still poorly understood. Tumourigenesis is generally considered a multistep process in which multiple genetic alterations occur, eventually reflected in abnormalities of the cellular DNA content. Macroscopical features such as tumour size and tumour architecture (tubular, tubulovillous, or villous) are correlated wit the chance of malignancy in the lesion. Grade of dysplasia can be considered an indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 39 publications
2
16
1
Order By: Relevance
“…In addition, individuals with rectal adenomas were twice as likely to have Ki-ras mutations compared with those with distal colonic adenomas ( Table 2). Univariate analyses of the relationships among adenoma size, degree of dysplasia, histology, and Ki-ras mutation showed positive associations with point estimates similar to those reported in the literature (15)(16)(17)(18)(44)(45)(46)(47)(48)(49)(50)(51). However, because these characteristics are highly correlated, multivariate analysis was required to assess the independent effect of each and showed that the presence of tubulovillous histology (OR, 4.19; 95% CI, 2.62-6.68) or of villous histology (OR, 5.45; 95% CI, 2.28-13.03) was strongly related to Ki-ras mutation as compared with tubular adenomas.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…In addition, individuals with rectal adenomas were twice as likely to have Ki-ras mutations compared with those with distal colonic adenomas ( Table 2). Univariate analyses of the relationships among adenoma size, degree of dysplasia, histology, and Ki-ras mutation showed positive associations with point estimates similar to those reported in the literature (15)(16)(17)(18)(44)(45)(46)(47)(48)(49)(50)(51). However, because these characteristics are highly correlated, multivariate analysis was required to assess the independent effect of each and showed that the presence of tubulovillous histology (OR, 4.19; 95% CI, 2.62-6.68) or of villous histology (OR, 5.45; 95% CI, 2.28-13.03) was strongly related to Ki-ras mutation as compared with tubular adenomas.…”
Section: Resultssupporting
confidence: 80%
“…Several smaller studies, generally using univariate analyses, have investigated the relationships among Ki-ras mutation and histology, size, and grade of dysplasia. Many, but not all, show a significant association between Ki-ras mutation and adenoma size (16,17,44,45) or more advanced histology (15,18,(46)(47)(48)(49)(50)(51)58). HGD has also been associated with Ki-ras mutation in some (17,44), but not all of these studies (16,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TP53 mutations have been reported to show intratumoral heterogeneity in intramucosal carcinomas but were homogeneous throughout invasive carcinomas (Kuwabara et al, 1998). Colorectal adenomas were also found to be heterogeneous for KRAS mutations and aneuploidy (Giaretti et al, 1996;Saraga et al, 1997). Thus, although mutational heterogeneity is present in several genes in microsatellite stable colorectal adenomas, it does not seem to be a common feature in carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…CRC development is a result of acquisition of multiple genetic changes such as mutations of tumor suppressor genes and various prooncogenes. In recent studies, K-ras mutations were detected in rate of 30% -50% in colorectal adenocarcinomas [2][3][4][5][6][7][8][9][10][11][12]. K-ras gene is located on chromosome 12 and encodes G protein showing GTPase activity [2].…”
Section: Introductionmentioning
confidence: 99%